Cultura e tecnologia : estudo tecnomorfológico das indústrias líticas lascadas do Sítio Arqueológico Buritizeiro/MG - Tiago Moreira Alves (2010)
This dissertation describes and analyzes the lithic industry identified in the Caixa D’água archaeological site, in Buritizeiro, a municipality located on the banks of the São Francisco River. It is an open-air prehistoric site, quite disturbed by recent occupations and impacts, whose earliest dates go back 10,000 years before the present. In terms of landscape, the site has a relatively flat topography, in higher sections of the margins, formed by a silt-clay cover superimposed on the “arcósio”– a kind of feldspathic sandstone abundant in the region. In addition to the lithic material, burials, coals, bone material, among others, were identified. The study sought to demonstrate, through the technique of analysis of operating sequence, the variations in the economy of the raw material, techniques and methods, which could reflect the different forms of cultural occupation of this archaeological site. The most abundant lithic industries are pebbles, “arcósio” and, to a lesser extent, sílex and quartz. The raw material management strategies demonstrated a knowledge focused on maximizing the resource through the technique known as pebble slicing and, in this sense, allowed us to propose hypotheses about the different occupations and modes of relationship between human beings and the environment throughout the almost 8,000 years of occupation at this site.